From phylogenomics to breeding: Can universal target capture probes be used in the development of SNP markers for kinship analysis? - Kedra M. Ousmael; Ole K. Hansen (Applications in Plant Sciences)
Abstract Premise Leveraging DNA markers, particularly single‐nucleotide polymorphisms (SNPs), in parentage analysis, sib‐ship reconstruction, and genomic relatedness analysis can enhance plant breeding efficiency. However, the limited availability of genomic information, confined to the most commonly used species, hinders the broader application of SNPs in species of lower economic interest (e.g., most tree species). We explored the possibility of using universal target capture probes, namely Angiosperms353, to identify SNPs and assess their effectiveness in genomic relatedness analysis. Methods We tested the approach in 11 tree species, six of which had a half‐sib family structure. Variants were called within species, and genomic relatedness analysis was conducted in species with two or more families. Scalability via amplicon sequencing was tested by designing primers and testing them in silico. Results Adequate SNPs for relatedness analysis were identified in all species. Relatedness values from Angiosperms353‐based SNPs highly correlated with those from thousands of genome‐wide DArTseq SNPs in Cordia africana, one of the species with a family structure. The in silico performance of designed primers demonstrated the potential for scaling up via amplicon sequencing. Discussion Utilizing universal target capture probes for SNP identification can help overcome the limitations of genomic information availability, thereby enhancing the application of genomic markers in breeding plant species with lower economic interest.